The CEV Model and Its Application in a Study of Optimal Investment Strategy. (12th August 2014) - Wang, Aiyin; Yong, Ls; Wang, Yang; Luo, Xuanjun
Abstract : The constant elasticity of variance ( CEV ) model is used to describe the price of the risky asset. Maximizing the expected utility relating to the Hamilton-Jacobi-Bellman ( HJB ) equation which describes the optimal investment strategies, we obtain a partial differential equation. Applying the Legendre transform, we transform the equation into a dual problem and obtain an approximation solution and an optimal investment strategies for the exponential utility function.